Thermal and alkaline pre-treatments of inoculum halt methanogenesis and enable cheese whey valorization by batch acidogenic fermentation - de Almeida, Maria Paula Giulianetti [UNESP]; Mondini, Camille; Bruant, Guillaume; Tremblay, Julien; Weissbrodt, David G.; Mockaitis, Gustavo [UNESP] (Wiley, 2024)
BACKGROUND: Carboxylates such as volatile fatty acids (VFA) can be produced by acidogenic fermentation (AF) of dairy wastes including cheese whey, a massive residue produced at 160.67 million m3 of which 42% are not valorized and impact the environment. In mixed-culture fermentations, selection pressures can favor AF and halt methanogenesis. In this study, inoculum pre-treatment was evaluated as a selective pressure for AF demineralized cheese whey in batches. Alkaline (NaOH, pH 8.0, 6 h) and thermal (90 °C for 5 min, ice-bath until 23 °C) pre-treatments were tested with batch operations runs at initial pH 7.0 and 9.0, food-to-microorganism (F/M) ratios of 0.5 to 4.0 g COD g−1 VS, and under pressurized (P) and nonpressurized (NP) headspace, in experiments duplicated in two different research institutes. RESULTS: Acetic acid was highly produced on both Unicamp and TU Delft samples (1.36 and 1.40 g CODAcOH L−1, respectively), at the expense of methanogenesis by combining a thermal pre-treatment of inoculum with a NP batch operation started at pH 9.0. Microbial communities comprising VFA and alcohol producers, such as Clostridium, Fonticella and Intestinimonas, and fermenters such as Longilinea and Leptolinea. The lipid-accumulating Candidatus microthrix was observed in both bulk material and foam. Despite the absence of methane production, Methanosaeta were detected within the microbial community. An F/M ratio of 0.5 g COD g−1 VS led to the best VFA production of 1769.4 mg L−1. CONCLUSION: Overall, inoculum thermal pre-treatment, initial pH 9.0 and NP headspace acted as a selective pressure for halting methanogenesis and producing VFAs, valorizing cheese whey via batch acidogenic fermentation. © 2024 Society of Chemical Industry (SCI).
Keywords: acidogenic fermentation; alkaline; cheese whey; physicochemical pre-treatments; thermal; volatile fatty acids